Administration of Intravenous Inf liximab for Prevention of Peritoneal Adhesions Formation in Rats - Saman Nikeghbalian; Homeira Vafaei; Farid Moradian; Kourosh Kazemi; Nader Tanideh; Leila Shayan; Zahra Nikeghbalian (Bulletin of Emergency and Trauma, 2015)
Objectives: To investigate the effects of intravenous infliximab in preventing the formation of peritoneal adhesions in an animal model of rat. Methods: This was an experimental study being performed in animal laboratory of Shiraz University of Medical Sciences during 2012. Sixty albino rats were randomly assigned in to three groups by Random Design Method. The first group received single infliximab injection (n=20), the second one received double infliximab injection (n=20) and the third received nothing (n=20), after receiving intra-peritoneal injection of talc for induction of peritoneal adhesions. All the animals were sacrificed after 6 weeks and the peritoneal adhesions were evaluated according to Nair classification. Results: We observed that the mean adhesion grade was lower in those who received double dose of infliximib when compared to single dose and controls. However the difference did not reach a significant value ( p=0.178). The grade of peritoneal adhesion was also comparable between the three study groups ( p=0.103). The mean number of 1st WBC count was also comparable between three study groups ( p=0.382). We observed that 2nd WBC count was also comparable between two study groups ( p=0.317). Conclusion: Administration of intravenous infliximab after intraabdominal surgicalprocedures would not prevent the formation of peritoneal adhesions in animal model of albino rat.